2008
DOI: 10.2337/db07-0893
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Peptide Endothelin-1 Links Fat Accumulation With Alterations of Visceral Adipocyte Lipolysis

Abstract: OBJECTIVE-Visceral obesity increases risk of insulin resistance and type 2 diabetes. This may partly be due to a regionspecific resistance to insulin's antilipolytic effect in visceral adipocytes. We investigated whether adipose tissue releases the vascular peptide endothelin-1 (ET-1) and whether ET-1 could account for regional differences in lipolysis.RESEARCH DESIGN AND METHODS-One group consisted of eleven obese and eleven nonobese subjects in whom ET-1 levels were compared between abdominal subcutaneous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 40 publications
6
61
1
2
Order By: Relevance
“…In this study, we show that a similar albeit smaller effect is observed in human fat cells. This effect is only observed after 24 h. Incubations with receptor-specific agonists suggest that the lipolytic effect of ET-1 is mediated through the ET A R. It has earlier been shown that ET-1 inhibits the antilipolytic effect of insulin after long-term treatment of visceral adipocytes through the selective activation of ET B R. 10 Taken together, these results demonstrate that ET-1 can affect lipolytic regulation at several levels and through activation of different receptors. Earlier studies have shown that circulatory levels of ET-1 are increased in obesity.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…In this study, we show that a similar albeit smaller effect is observed in human fat cells. This effect is only observed after 24 h. Incubations with receptor-specific agonists suggest that the lipolytic effect of ET-1 is mediated through the ET A R. It has earlier been shown that ET-1 inhibits the antilipolytic effect of insulin after long-term treatment of visceral adipocytes through the selective activation of ET B R. 10 Taken together, these results demonstrate that ET-1 can affect lipolytic regulation at several levels and through activation of different receptors. Earlier studies have shown that circulatory levels of ET-1 are increased in obesity.…”
Section: Discussionmentioning
confidence: 52%
“…10,[20][21][22][23][24] We have recently shown that s.c. adipose tissue, which is the major adipose region, might contribute to the elevated levels of ET-1 in the obese state. 10 This study shows that the expression of ET-1 mRNA is higher in s.c. adipose tissue compared with OM adipose tissue, whereas ETR expression is similar in the two depots . Expression analysis in cells from the different compartments in s.c. adipose tissue suggests that the major cellular source of ET-1 is present in the stroma vascular portion, mostly constituting endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations